Application of «away» for coccidiosis treatment - Yu. V. Bakhtiyarova; N. A. Lutfullina; V. V. Andriyashin; S. N. Egorova; M. H. Lutfullin; I. V. Galkina (Российский паразитологический журнал, 2016)
Efficiency of «away» at eimeriosis is studied. It is received high efficiency of the drug in a dose of 10 mg/kg at eimeriosis of chickens, rabbits and pigs. Acute toxicity of the drug is 160 mg/kg. «Away» belongs to the third class of moderately dangerous substances.